PENDAMPINGAN SISWA SDK ENDE 2 UNTUK PENCEGAHAN DAN PENGURANGAN PERILAKU BULLYNG - Maria Finsensia Ansel; Maria Purnama Nduru (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2020)
The problems that occurred in SDK Ende 2 were found from the results of filling out a questionnaire on bullying behavior socialization activities carried out in the even semester of the 2018/2019 academic year, it is known that almost some students at SDK Ende 2 experienced bullying experienced both as victims and as perpetrators. Bullying behavior that occurs is in the form of verbal bullying and physical bullying. The aim of mentoring students at SDK Ende 2 is to prevent and reduce bullying so that it can reduce and eliminate bullying that occurs in the school environment. The implementation method used is the discussion method with the stages carried out, namely the initial or planning stage, the implementation stage and the final stage. The results obtained from the series of activities above are expected that each student realizes that friendship, love, and assistance, respect and love between friends are behaviors that must be fostered properly so as to prevent or reduce bullying and screaming behavior. getting a winner is used as a slogan used by the school to remind students not to bully at school.